Microbial response to copper oxide nanoparticles in soils is controlled by land use rather than copper fate. Issue 12 (11th November 2021) - Rippner, Devin A.; Margenot, Andrew J.; Fakra, Sirine C.; Aguilera, L. Andrea; Li, Chongyang; Sohng, Jaeeun; Dynarski, Katherine A.; Waterhouse, Hannah; McElroy, Natalie; Wade, Jordon; Hind, Sarah R.; Green, Peter G.; et al.
Abstract : Microbial response to copper oxide nanoparticles in soils is controlled by land use rather than copper fate. Abstract : Copper (Cu) products, including copper oxide nanoparticles (nCuO), are critically important agricultural fungicides and algaecides. Foliar application onto crops and subsequent aerosol drift of these Cu products, especially nCuO, on to soil may alter nutrient cycling and microbial communities in both managed and unmanaged environments. We measured the influence of land use on soil microbial biomass and respiration in response to the addition of nCuO to an alluvial soil. Different land uses included grassland, forest and both organic and conventional managed row crops. Soil samples were amended with 1000 mg Cu per kg soil as CuCl2, 16 nm CuO (16nCuO), 42 nm CuO (42nCuO), and larger than nanoparticle sized bulk CuO (bCuO). Copper availability immediately increased in all soils following Cu addition in the order of CuCl2 > 16nCuO > 42nCuO > bCuO. After 70 days Cu availability was diminished across land uses and lowest in soils treated with bCuO. Using X-ray absorption near edge structure (XANES) spectroscopy, we determined that the relatively high availability of Cu after treatment with nanoparticle sized CuO was due to the dissolution of CuO particles and subsequent adsorption by soil materials. Respiration, an indicator of microbial activity, was suppressed by Cu additions, especially CuCl2 . Copper effects on soil microbial biomass were sensitive to land use. In agricultural soils, microbial biomass was unaltered by Cu form, regardless of concentration, whereas in unmanaged soils, it decreased following exposure to CuCl2 and 42nCuO. Our results suggest that land use history has little impact on Cu chemical fate in soils, but strongly modulates microbial response to Cu exposure. These results are especially important for organic agricultural systems where copper fungicides are widely used but may suppress microbial mineralization of nutrients from soil organic matter.